Investigators’ and Prosecutors’ Perceptions of Collaborating With Victim Advocates on Sexual Assault Casework - Gaines, D. Cody (Criminal justice policy review, 2017)
Despite the importance of strong partnerships between victim advocates and criminal justice officials, few studies have examined criminal justice officials’ perspectives on collaborating with victim advocates. Officials’ perspectives on advocates’ roles in the investigation and prosecution of sexual assaults are measured to understand the barriers to collaboration and strengths that can be capitalized upon. A sample of sexual assault investigators from a large police department were interviewed using a structured questionnaire. A sample of prosecutors from the jurisdiction, experienced in processing sexual assault cases, responded to paper-and-pencil surveys. Findings reveal that officials believe advocates make positive contributions to the justice system process through effective communication and by supporting victims and their families. Barriers to strong partnerships include concerns about role conflicts and advocate involvement in criminal investigations. Reform efforts can use these findings through explicit work to capitalize on perceived strengths and overcome barriers.